The Effect of ICU Out-of-Hours Admission on Mortality: A Systematic Review and Meta-Analysis*. Issue 2 (February 2018) - Galloway, Megan; Hegarty, Aoife; McGill, Sarah; Arulkumaran, Nishkantha; Brett, Stephen J; Harrison, David
Abstract : Objectives: Organizational factors are associated with outcome of critically ill patients and may vary by time of day and day of week. We aimed to identify the association between out-of-hours admission to critical care and mortality. Data Sources: MEDLINE (via Ovid) and EMBASE (via Ovid). Study Selection: We performed a systematic search of the literature for studies on out-of-hours adult general ICU admission on patient mortality. Data Extraction: Meta-analyses were performed and Forest plots drawn using RevMan software. Data are presented as odds ratios ([95% CIs], p values). Data Synthesis: A total of 16 studies with 902, 551 patients were included in the analysis with a crude mortality of 18.2%. Fourteen studies with 717, 331 patients reported mortality rates by time of admission and 11 studies with 835, 032 patients by day of admission. Admission to ICU at night was not associated with an increased odds of mortality compared with admissions during the day (odds ratio, 1.04 [0.98–1.11]; p = 0.18). However, admissions during the weekend were associated with an increased odds of death compared with ICU admissions during weekdays (1.05 [1.01–1.09]; p = 0.006). Increased mortality associated with weekend ICU admissions compared with weekday ICU admissions was limited to North American countries (1.08 [1.03–1.12]; p = 0.0004). The absence of a routine overnight on-site intensivist was associated with increased mortality among weekend ICU admissions compared with weekday ICU admissions (1.11 [1.00–1.22]; p = 0.04) and nighttime admissions compared with daytime ICU admissions (1.11 [1.00–1.23]; p = 0.05). Conclusions: Adjusted risk of death for ICU admission was greater over the weekends compared with weekdays. The absence of a dedicated intensivist on-site overnight may be associated with increased mortality for acute admissions. These results need to be interpreted in context of the organization of local healthcare resources before changes to healthcare policy are implemented. Abstract : Supplemental Digital Content is available in the text.